Endoplasmic reticulum stress attenuation promotes bovine oocyte maturation in vitro. Issue 4 (April 2020) - Khatun, Hafiza; Wada, Yasuhiko; Konno, Toshihiro; Tatemoto, Hideki; Yamanaka, Ken-ichi
Abstract : We have previously reported that regulation of endoplasmic reticulum (ER) stress during in vitro culture acutely increases bovine embryo developmental rate and cryotolerance; these data indicate that ER stress is a critical factor reducing the quality of in vitro -produced embryos. In the current follow-up study, we examined whether ER stress attenuation during in vitro maturation influences meiotic maturation, oocyte quality, and subsequent embryonic development. Bovine cumulus oocyte complexes (COCs) derived from slaughterhouse ovaries were matured with or without tauroursodeoxycholic acid (TUDCA), a selective inhibitor of ER stress (0, 50, 100, and 200 µM) for 22 h followed by in vitro fertilization, and zygotes were cultured for 8 days. Of the different doses of TUDCA, 100 μM TUDCA significantly increased the maturation rate, and decreased reactive oxygen species in denuded oocytes, and appeared lower number of apoptotic cells in matured COCs. Subsequently, treatment of TUDCA (100 µM) decreased the localization and amount of GRP78/BIP protein level as well as ER stress ( GRP78/BIP, PERK, IER1, ATF4, and XBP1 ) and apoptosis ( CHOP and BAX )-related gene expression, while it increased the anti-apoptotic gene BCL2 level in matured COCs. Moreover, addition of TUDCA (100 µM) during IVM significantly improved the blastocyst formation rate (43.6 ± 1.8% vs 49.7 ± 1.3%) and decreased the number of apoptotic cells (7.7 ± 1.1% vs 5.03 ± 0.6%) in blastocysts. These findings suggest that the presence of ER stress during maturation impairs the developmental competence of bovine COCs and that this process can be reversed by TUDCA.